นิทานในหนังสือนิทานแนว edutainment ภาษาไทย: การศึกษาพลวัตของนิทานในปริบทสังคมไทยร่วมสมัย - ภักดีผาสุข ศิริพร (Journal of Letters, 2016)
หนังสือนิทานแนว edutainment ผลิตขึ้นเพื่อใช้เป็นสื่อในการเรียนรู้ที่เน้นทั้ง การถ่ายทอดความรู้เชิงวิชาการและสร้างเสริมทักษะความชาญฉลาดในด้านต่างๆ ไปกับการให้ความบันเทิง หนังสือนิทานกลุ่มนี้มีความน่าสนใจในแง่การนำคติชนไปใช้ในปริบทสังคมไทยร่วมสมัย บทความวิจัยเรื่องนี้มีวัตถุประสงค์เพื่อศึกษาพลวัตของนิทานในหนังสือนิทานแนว edutainment ภาษาไทยทั้งในระดับตัวบทและการประยุกต์ใช้ตัวบท โดยใช้แนวคิดเรื่องสหบทและสหวาทกรรม รวมทั้งแนวคิดเรื่องวัฒนธรรมประชานิยมและลักษณะคู่ผสานเป็นกรอบในการศึกษาข้อมูลจากหนังสือนิทานแนว edutainment จำนวน 132 เล่ม ผลการศึกษาพบว่าในระดับตัวบท ลักษณะพลวัตที่พบในหนังสือนิทานเหล่านี้คือการจัดการตัวบทเพื่อการนำเสนอเนื้อหาที่เป็นความรู้เชิงวิชาการซึ่งพบ 3 ลักษณะ ได้แก่ การสร้างนิทานใหม่ การดัดแปลงหรือประยุกต์ใช้นิทานเก่าและการสร้างสหบทและสหวาทกรรม ส่วนพลวัตในแง่การใช้นั้นได้แก่ การใช้นิทานเพื่อวัตถุประสงค์ในการถ่ายทอดความรู้เชิงวิชาการและการใช้นิทานในลักษณะใหม่ๆ ลักษณะสหบทและสหวาทกรรมที่พบในหนังสือนิทานแนว edutainment ภาษาไทยเป็นเครื่องบ่งบอกและสะท้อนถึงความเปลี่ยนแปลงบางอย่างในสังคมไทยร่วมสมัยคือการแผ่ขยายกิจกรรมการเรียนตามระบบหลักสูตรการศึกษาในโรงเรียนสู่กิจกรรมการเรียนรู้ในภาคครัวเรือน ลักษณะดังกล่าวส่วนหนึ่งน่าจะเป็นผลเนื่องมาจากความต้องการเตรียมความพร้อมทางการศึกษาให้แก่บุตรหลานเพื่อที่จะสามารถแข่งขันกับผู้อื่นได้และได้รับโอกาสที่ดีกว่าในสังคม Tales in Edutainment Story Books in Thai: A Study of the Dynamics in the Context of Contemporary Thai Society Siriporn Phakdeephasook Assistant Professor, Department of Thai, Faculty of Arts, Chulalongkorn University Edutainment story books are produced for use as learning media which entertain learners while also imparting academic knowledge and developing useful intellectual skills. What is interesting about these books is their use of folklore in the context of contemporary Thai society. This research article examines the dynamics of tales in edutainment story books in Thai at the textual and application levels. The research frameworks used to study tales from 132 books include the concepts of intertextuality, interdiscursivity, popular culture and bi-sociation. It is found that at the textual level, the dynamic aspect of these books, namely the management of texts for the presentation of academic knowledge, is of three types: creation of new tales, adaptation of old tales and creation of intertextuality and interdiscursivity. At the application level, the dynamics are reflected in the use of tales to provide academic knowledge and in new forms. Intertextuality and interdiscursivity found in edutainment story books in Thai indicate and reflect some changes in contemporary Thai society. Learning activities under the educational curriculum have been extended to households. This is probably partly caused by parents’ need to prepare their children to compete with their peers for better educational opportunities.